DAMPAK KONVERSI LAHAN TERHADAP LINGKUNGAN LAHAN PERTANIAN DAN STRATEGI ADAPTASI PETANI DI KECAMATAN MEJAYAN - Pepekai, Agus Eko Raharjo (Magister Pendidikan IPA, UNCEN, 2015)
This study aimed to : 1) to assess the impact of the conversion agricultural land to the environmental condition of agricultural land as well as socio-economic conditions of farmers; 2) to analyze what strategies adaptation of the farmers in facing the conversion of agricultural land; 3) to analyze the effect of conversion land to the farmer adaptation strategies. This study has a survey method by taking a proportional sampling of each farmer status individually. The total samples of 96 respondents are 46 respondent peasant land owners, tenant farmers 31 respondents, and 19 respondents laborer. The data use consists of primary data, in a questionnaires and in-depth interviews, then secondary data from relevant agencies. Methods of data analysis use a quantitative descriptive analysis, the chi squared test and contingency coefficient. The results show conversion of agricultural land in the district of Mejayan has a negative effect to the wetland environment, such as the less land farming, irrigation canals damage, and declining soil fertility due to household waste. There are different adaptation strategy of each farm household; 56.5% land owner applying accumulation strategies, 87.1% of tenant farmers implementing consolidation strategies and 84.2% of farm workers applying survival strategies. The condition of socio-economic with contingency coefficient value 0.557 and the ownership assets with a contingency coefficient value 0,462 influence really to the farmer adaptation strategies, in both factors status socio economic condition give a stronger influence to the form of farmer adaptation strategies. Keywords: Cooperative Learning Model Think Pair Share, Understanding, Learning Outcomes, Probability